Peran inseminasi buatan (IB) terhadap sistem perkawinan di kelompok tani ternak lembu karomah kecamatan taluditi kabupaten pohuato - Amin, Mohamad Nur (Jambura Journal of Animal Science, 2019)
ABSTRACTThis study aims to determine the role of artificial insemination (IB) on the marriage system in the group of caromah cattle farmers in Taluditi Sub-District, Pohuwato Regency. The livestock population of 60 cows consisting of A 32 cages and enclosure B 28 tails. The analysis used was descriptive analysis to get the percentage and average number of pregnancies. Parameters observed include: Service Per Conception (S / C) and Conception Rate (C / R). The results showed that (Service Per Conception) obtained results at enclosure A, the S / C value was 1.7 times, and at enclosure B the S / C value was 1.7 times. The percentage of pregnancy (Conception Rate) is obtained at A cage 79% and the result in cage B is C / R value of 67%. The results obtained are strongly influenced by 4 factors, namely; namely frozen semen, female cattle as IB acceptors, inseminator skills and zooteknis knowledge of farmers. The conclusion of this study is that the success rate of Artificial Insemination in Taluditi District, Pohuwato Regency can be categorized as good.Keywords: Artificial Inseminasai, Service Per Conception and Conception Rate